Implementation of improvement in the banana packing process: case applied in urabá farm (Antioquia) - Trespalacio González, Anderson Manuel; Trespalacio González, Anderson Manuel; Trespalacio González, Anderson Manuel (Corporación universitaria Americana, 2022)
The objective of this work is to identify the possible difficulties in the banana packing process developed by the Kalamary farm, located in Urabá Antiqueño, in order to implement improvements in the process so as to offer a better yield in the plant and increase the farm's production.To achieve this purpose, field work was carried out to obtain preliminary information on the process, which was later used to carry out a basic simulation that reflected the reality of the banana packing process. Finally, a final simulation was carried out in which the improvements were implemented, showing an increase in the productive yield of the Kalamary farm.